Decision-making: From 'participatory citizenship' to active citizenship. A feminist activist ethnography of parent-school relations in a DEIS School context - OSULLIVAN, KARIN (Trinity College Dublin. School of Nursing & Midwifery. Discipline of Nursing, 2019)
Background Citizen participation in policy decision-making is a key principal of government as part of creating an inclusive society. The critical policy literature on the discourse of social inclusion/exclusion argues that this dialectic is constitutive of a mental model of a benign inside of society in contrast to a problematic outside. This is further argued to orientate policy work towards bringing the excluded inwards away from the problematic sphere of exclusion, but in to what is actually an unequal sphere of inclusion. Orientated this way, the effect of policy work on the reproduction of inequality and exclusion, is argued to be made invisible. Alongside Ireland s long-existing social inequality, this literature sets the backdrop for this critical inquiry into what is occurring in the policy-work of participation . Problem or research question This study critically explores the meaning of decision-making as it is constituted in the discourse and practices of neoliberal policy-making in Ireland. In order to examine this question, the aims of the study are to inquire into how this meaning is informed, how this relationship is held in place, and the effect this has on those lower down on the social hierarchy. The study also explores the implications of these processes for society more generally. Finally, the study examines if ideas for an alternative and inclusive process of decision-making exist, and if so what this might look like. Methodology: participants, setting, procedure of study, data analysis. The study uses a feminist activist ethnographic approach to inquiry for exploring the study problem in the micro context of school-parent relations. Participant observation was undertaken in a DEIS primary school setting, over a nine month period. Interviews and a focus group were carried out with school staff, and with parents. Data analysis was an iterative process of moving between field, theory, and writing. The research was underpinned by a feminist ethics of care, reciprocity, empowerment and emancipation. Findings Study findings make visible conditions constitutive of school-parent relations that are de-politicising and reproductive of inequality. This was evident in a complex context of power relations, within and between the government, school and parents, argued to be informed by an intensification of a neoliberal market logic. While productive of an ideal type of decision-making subject, these processes were also shown to be constitutive of an inequality of access to that position. This was held in place in relations that make up the wider agenda-setting arena, notably characterised by support and kindness, but relations that were individualising and thus simultaneously silencing of dissent. An added complexity was found where perspectives shaped by concerns of risk and respectability held this unequal and de-politicised dynamic in place. The study forecasts an increasing social polarisation should we continue along this trajectory. Notably, resistance to the status quo was evident among parents and/or the school. Based on the constitutive nature of social relations this offers us hope in that we can choose to create an alternative future. Drawing from knowledge learned from those excluded from decision-making, ideas for informing policy work and mapping a collective way forward are identified. Conclusion For real inclusion to occur policy researchers and practitioners must begin their work from a presupposition of equality.
APPROVED
Keywords: Policy Work; Neoliberalism; Subjectivity; Inequality